Descendants of the first stars: the distinct chemical signature of second-generation stars. Issue 2 (7th May 2018) - Hartwig, Tilman; Yoshida, Naoki; Magg, Mattis; Frebel, Anna; Glover, Simon C O; Gómez, Facundo A; Griffen, Brendan; Ishigaki, Miho N; Ji, Alexander P; Klessen, Ralf S; O'Shea, Brian W; Tominaga, Nozomu
ABSTRACT: Extremely metal-poor (EMP) stars in the Milky Way (MW) allow us to infer the properties of their progenitors by comparing their chemical composition to the metal yields of the first supernovae. This method is most powerful when applied to mono-enriched stars, i.e. stars that formed from gas that was enriched by only one previous supernova. We present a novel diagnostic to identify this subclass of EMP stars. We model the first generations of star formation semi-analytically, based on dark matter halo merger trees that yield MW-like haloes at the present day. Radiative and chemical feedbacks are included self-consistently and we trace all elements up to zinc. Mono-enriched stars account for only ∼1 per cent of second-generation stars in our fiducial model and we provide an analytical formula for this probability. We also present a novel analytical diagnostic to identify mono-enriched stars, based on the metal yields of the first supernovae. This new diagnostic allows us to derive our main results independently from the specific assumptions made regarding Pop III star formation, and we apply it to a set of observed EMP stars to demonstrate its strengths and limitations. Our results may provide selection criteria for current and future surveys and therefore contribute to a deeper understanding of EMP stars and their progenitors.